A shared Asian origin of the triple-mutant dhfr allele in Plasmodium falciparum from sites across Africa - Maïga, O.; Djimdé, A.A.; Hubert, V.; Renard, E.; Aubouy, A.; Kironde, F.; Nsimba, B.; Koram, K.A.; Doumbo, O.K.; Le Bras, J.; Clain, J. (Journal of Infectious Diseases 196(1):165-72, 2007)
Usefulness of sulfadoxine-pyrimethamine as first-line therapy for uncomplicated Plasmodium falciparum malaria and intermittent preventive treatment in pregnancy throughout sub-Saharan Africa is compromised by the spread of dhfr alleles associated with pyrimethamine resistance. A predominant haplotype associated with the N51I+C59R+S108N triple-mutant dhfr allele has been reported recently in 4 African countries. A more comprehensive picture of the evolution of this mutant allele in Africa is lacking. METHODS: Seventy-five P. falciparum isolates carrying the wild-type dhfr allele and 204 carrying the triple-mutant dhfr allele from 11 African countries were selected. The genetic diversity of the chromosomes bearing these alleles was analyzed with 4 microsatellite markers closely linked to the dhfr gene. RESULTS: Seventy-three different 4-locus haplotypes carrying the wild-type dhfr allele were found. By contrast, 175 (85%) of 204 isolates carrying the triple-mutant dhfr allele shared a unique haplotype, identical to the one identified in Thailand. For the remaining triple-mutant isolates and one isolate with the quadruple-mutant dhfr allele N51I+C59R+S108N+I164L), haplotypes were closely related to the predominant haplotype by mutation or recombination. CONCLUSIONS: Migration of parasites carrying an ancestral triple-mutant dhfr allele drives the spread of dhfr alleles associated with pyrimethamine resistance throughout West and Central Africa.